Effect of leukocytes on semen quality in men from primary and secondary infertile couples: A cross‐sectional study - Shiwei Fan; Yuanqi Zhao; Zeling Zhang; Huiru Wang; Yifu Hou; Shun Bai; Ran Liu; Bo Xu (Health Science Reports, 2023)
Abstract Background and Aims Leukocytospermia (LCS) is a known cause of male infertility. However, the relationship between seminal leukocytes and semen quality among infertile couples remains controversial. This study aims to investigate the association between semen quality and LCS in male partners of infertile couples. Methods Semen samples were collected from 512 men who asked for a fertility evaluation in a reproductive center in China. Seminal leukocytes were counted following peroxidase staining with benzidine. Other semen parameters were compared in subfertile men with and without LCS. Results Poor semen quality (e.g., low semen volume, sperm concentration, and sperm progressive/total motility) was observed among men with LCS compared to those without LCS. Men with LCS had a higher risk of low sperm progressive motility (OR = 0.99, 95% CI = 0.98−0.99, p = 0.02) and total motility (OR = 0.99, 95% CI = 0.98−0.99, p = 0.02), even after adjustment for potential confounders (both OR = 0.99, 95% CI = 0.98−0.99, p = 0.03). Lower sperm viability was observed in LCS from male partners of secondary couples, while no significant difference in semen parameters was found between men with and without LCS in male partners of primary infertile couples. Low sperm motility and viability were associated with LCS in men from secondary infertile couples after adjusting for confounders (OR = 0.97, 95% CI = 0.95−0.99, p = 0.04; OR = 0.94, 95% CI = 0.89−0.99, p = 0.04, respectively). Conclusions Our findings indicate that a higher risk of abnormal semen parameters was correlated with an increased number of leukocytes in men from secondary infertile couples.